Efficacy of Music Therapy in Treatment for the Patients with Alzheimer's Disease. (26th September 2012) - Fukui, H.; Arai, A.; Toyoshima, K.
Abstract : We report that music therapy is effective in the treatment of Alzheimer's disease. We found that the secretion of 17β -estradiol and testosterone, hormones that are supposed to have preventive effects on Alzheimer's disease, is significantly increased by music therapy. During the sessions, patients with Alzheimer's disease were allowed to listen to music and songs with verbal contact from the therapist. It was found that problematic behaviors such as poriomania (fugue) had decreased. Music therapy has the potential as an alternative treatment for adverse hormone replacement therapy.